Vaccination for Inflammatory Bowel Disease Patients - Yunihastuti, Evy (The Indonesian Society for Digestive Endoscopy, 2022)
Inflammatory bowel disease (IBD) patients have an increased rate of some vaccine-preventable infection during their course of disease. However, the coverage of vaccination is still low. Many physicians often do not feel comfortable or confidence offering vaccination to IBD patients. Vaccine effectiveness can be altered by the immune dysregulation condition and immunosuppressive therapy that IBD patients use. There are also some concerns about IBD flare after vaccination and potential adverse events related to live vaccines. Nonetheless, offering vaccines and obtaining vaccination history is necessary for health care maintenance of IBD patients, especially those using immunosuppressive therapy.